2001
DOI: 10.1007/bf02255972
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, metabolism of ethanol and alcohol-related diseases

Abstract: Alcohol-induced oxidative stress is linked to the metabolism of ethanol. Three metabolic pathways of ethanol have been described in the human body so far. They involve the following enzymes: alcohol dehydrogenase, microsomal ethanol oxidation system (MEOS) and catalase. Each of these pathways could produce free radicals which affect the antioxidant system. Ethanol per se, hyperlactacidemia and elevated NADH increase xanthine oxidase activity, which results in the production of superoxide. Lipid peroxidation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
92
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(99 citation statements)
references
References 67 publications
5
92
0
2
Order By: Relevance
“…26) Oxidative stress is characterized by increased lipid peroxidation and/or altered nonenzymatic and enzymatic antioxidant systems. The effects of exposing mice to the chronic regime of alcohol on various antioxidant defences and lipid peroxides were investigated in the liver.…”
Section: Resultsmentioning
confidence: 99%
“…26) Oxidative stress is characterized by increased lipid peroxidation and/or altered nonenzymatic and enzymatic antioxidant systems. The effects of exposing mice to the chronic regime of alcohol on various antioxidant defences and lipid peroxides were investigated in the liver.…”
Section: Resultsmentioning
confidence: 99%
“…8,9) Oxidative stress is characterized by increased lipid peroxidation and/or altered nonenzymatic and enzymatic antioxidant systems. However, conflicting results are reported in the literature concerning oxidative stress following chronic ethanol treatment in rats.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress is known to play an important role in the pathogenesis of ethanol-induced liver injury. 8,9) Several experimental [10][11][12][13] and clinical 14) studies have shown that ethanol ingestion alters the prooxidant-antioxidant balance in the organism. Therefore the potential role of several substances such as antioxidants 15,16) and thiol compounds 5,12,13) has been investigated in ethanol-induced liver injury.…”
mentioning
confidence: 99%
“…The availability of both transgenes has made it possible to examine the precise mechanism(s) of acetaldehyde in alcoholic tissue and cell injury. Although several hypotheses have been postulated for alcohol toxicity including oxidative damage, lipid peroxidation and altered membrane property due to hydrophobic ethanol interaction with membrane components (23)(24)(25), the culprit toxin in alcoholic tissue and cell injury, has not been clearly identified and thus hindered proper treatment and prevention of alcoholic complications. Ethanol has been demonstrated to contribute to oxidative stress and enhanced peroxidation of lipids, protein, and DNA in a wide variety of organs, tissues, and cells (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Although several hypotheses have been postulated for alcohol toxicity including oxidative damage, lipid peroxidation and altered membrane property due to hydrophobic ethanol interaction with membrane components (23)(24)(25), the culprit toxin in alcoholic tissue and cell injury, has not been clearly identified and thus hindered proper treatment and prevention of alcoholic complications. Ethanol has been demonstrated to contribute to oxidative stress and enhanced peroxidation of lipids, protein, and DNA in a wide variety of organs, tissues, and cells (23)(24)(25)(26). Similarly, the ethanol metabolite acetaldehyde directly enhances free radical generation by its oxidation via aldehyde oxidase and/or xanthine oxidase with concurrent accumulation of superoxide (25,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%